2017
DOI: 10.3389/fmicb.2017.01826
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Lateral Flow Test for Detection and Differentiation of Cronobacter sakazakii Serotypes O1 and O2

Abstract: The ubiquitous and opportunistic pathogen Cronobacter sakazakii is responsible for severe meningitis, sepsis, and necrotizing enterocolitis in neonates and infants associated with ingestion of contaminated powdered infant formula (PIF). The current ISO method for isolation and detection of Cronobacter spp. is laborious, time-consuming and expensive. In this study, a multiplexed lateral flow test strip was developed to rapidly detect and simultaneously serotype O1 and O2 C. sakazakii serotypes. The assay is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This finding was in agreement with our previous survey in raw vegetables (Ling et al, 2018), but in disagreement with previous studies, in which C. sakazakii serotype O2 was the most dominant serotype in ready-to-eat foods in China (Xu et al, 2015) and powdered infant formula (PIF) (Fei et al, 2017b). It is worth noting that both serotypes O1 and O2 have been associated with clinical sources (Scharinger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was in agreement with our previous survey in raw vegetables (Ling et al, 2018), but in disagreement with previous studies, in which C. sakazakii serotype O2 was the most dominant serotype in ready-to-eat foods in China (Xu et al, 2015) and powdered infant formula (PIF) (Fei et al, 2017b). It is worth noting that both serotypes O1 and O2 have been associated with clinical sources (Scharinger et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those of Pan et al (2018), except that the strip tested in the present study showed no cross-reaction with Staphylococcus aureus, different from the report of Pan et al (2018). The reason for this may have been that the lipopolysaccharide adjuvant evaluated the specificity of the antibody generated (Scharinger et al, 2017).…”
Section: Reproducibility and Selectivity Of The Sers Immunochromatogr...mentioning
confidence: 99%
“…The immunochromatographic test strip, based on immunological recognition, has attracted increasing attention because of its high specificity and ease of use in on-site testing (Aragay et al, 2012;Hu et al, 2014;Koczula and Gallotta, 2016). However, the sensitivity and accuracy of the test strip need to be confirmed for pathogen detection (Scharinger et al, 2017;Pan et al, 2018). In test strip assays, gold nanoparticles (AuNP) are used to label the antibody, resulting in color changes upon interaction of the antibody with antigens (Bu et al, 2019;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This technology could be utilized to determine multiple HAI causing bacteria within the hospital environment [ 63 ]. A study conducted in 2017 by Scharinger et al showed the detection and serotyping of Cronobacter sakazakii a bacterium responsible for sepsis, meningitis and necrotising enterocolitis in infants [ 96 ]. This detection system utilized highly serotype specific monoclonal antibodies in a multiplex lateral flow format [ 40 ].…”
Section: Detection Systemsmentioning
confidence: 99%
“…Only the O1 and O2 strains showed colored test lines 1 and 2 respectively, all other strains only showed a colored control line. The entire process took approximately 15 min and has a limit of detection of approximately 10 8 to 10 9 cfu/mL [ 96 ]. Due to the quick processing time, it is an ideal example of how an LFA could be used as a rapid POC detection system.…”
Section: Detection Systemsmentioning
confidence: 99%